MANAGING EMPLOYEE ENGAGEMENT IN GENERATION Z - Eldes Willy Filatrovi; Khoirul Attiq (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study was to determine the effect of compensation equity and development opportunities as well as psychological meaningfulness on employee engagement. The study was conducted on 150 generation Z employees in Central Java. Analysis using SEM (AMOS) shows several findings: compensation fairness affects psychological meaningfulness; fairness compensation has no effect on employee engagement; career opportunities for psychological meaningfullness; Career opportunities have no effect on employee engagement; Psychological meaningfullness affects employee engagement ..